Rimonabant suppresses RNA transcription of hepatitis B virus by inhibiting hepatocyte nuclear factor 4α. (25th February 2020) - Sato, Asuka; Ono, Chikako; Tamura, Tomokazu; Mori, Hiroyuki; Izumi, Takuma; Torii, Shiho; Fauzyah, Yuzy; Yamamoto, Takuya; Morioka, Yuhei; Okuzaki, Daisuke; Fukuhara, Takasuke; Matsuura, Yoshiharu
Abstract: Chronic infection with hepatitis B virus (HBV) sometime induces lethal cirrhosis and hepatocellular carcinoma. Although nucleot(s)ide analogs are used as main treatment for HBV infection, the emergence of the drug‐resistant viruses has become a problem. To discover novel antivirals with low side effects and low risk of emergence of resistant viruses, screening for anti‐HBV compounds was performed with compound libraries of inhibitors targeting G‐protein‐coupled receptors (GPCRs). HepG2‐hNTCP C4 cells infected with HBV were treated with various GPCR inhibitors and harvested at 14 day postinfection for quantification of core protein in the first screening or relaxed circular DNA in the second screening. Finally, we identified a cannabinoid receptor 1 inhibitor, rimonabant, as a candidate showing anti‐HBV effect. In HepG2‐hNTCP C4 cells, treatment with rimonabant suppressed HBV propagation at the viral RNA transcription step but had no effect on entry or covalently closed circular DNA level. The values of half maximal inhibitory concentration, half maximal effective concentration, and selectivity index of rimonabant in primary human hepatocyte (PHH) are 2.77 μm, 40.4 μm, and 14.6, respectively. Transcriptome analysis of rimonabant‐treated primary hepatocytes by RNA sequencing revealed that the transcriptional activity of hepatocyte nuclear factor 4α (HNF4α), which is known to stimulate viral RNA synthesis, was depressed. By treatment of PHH with rimonabant, the expression level of HNF4α protein and the production of the messenger RNAs (mRNAs) of downstream factors promoted by HNF4α were reduced while the amount of HNF4α mRNA was not altered. These results suggest that treatment with rimonabant suppresses HBV propagation through the inhibition of HNF4α activity.